Compilation of annual mini SAMs for South Africa 1993-2013 in current and constant prices - Dirk van Seventer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We describe the construction of a series of mini Social Accounting Matrices (SAMs) for the period 1993-2013 in current and constant prices. A key feature of these SAMs is that they are all in exactly the same format across years as well as in terms of current and constant prices. In order to keep the dataset manageable while offering some level of detail that is meaningful for policy purposes, we adopt a disaggregation of 15 activities and commodities. Current price mini SAMs are converted into constant price mini SAMs using deflators that are derived from official data sources such as Statistics South Africa Quarterly GDP series and the South African Reserve Bank's Quarterly Bulletin.
Keywords: E16; 330; social accounting matrix; national accounts; supply table; use table; cross-entropy SAM estimation